Enhancing Organizational Learning through Social Media: Insights from Social Learning Theory - Marcel, Marcel; Kristiani, Evelline; Mudita, Damida Shu (Universitas Bina Darma, 2024)
This qualitative case study investigates social media and its effect on organizational learning within a technology manufacturing company. Seven participants, including a general manager and IT specialist, team leaders, frontline managers, and an HR coordinator, were interviewed through semi-structured interviews to get insights on the use of social media for organizational learning. The finding indicated that social media learning effectiveness is constrained by poor governance, lack of consistent leadership support, and technological enablers. There also are cultural challenges to overcome, such as generational differences and differing levels of digital literacy. By outlining the significant factors that need to be addressed for technology manufacturers to incorporate social media into their learning strategies fully, this study provides valuable practical advice on using social media for best organizational learning. For successful integration, the study indicates that strategic alignment and better digital literacy should exist. Future research should explore how these barriers might be overcome and test different social media approaches in various organizational contexts.